Occupational Eye Problems among the Workers of Patan Industrial State, Nepal - Adhikari, Anup; Aryal, Bhagwan; KC, Ram Bahadur; Khatiwada, Kamana; KC, Amit (Mangal Research Journal, 2025)
Occupational health is an essential public health area that promotes and safeguards workers’ physical, mental, and social well-being across all industries. This study focuses on workplace safety, particularly in developing countries like Nepal, where occupational safety and health (OSH) practices are often insufficient. This study aims to assess occupational health hazards, particularly the causes of vision problems, faced by workers in the Patan Industrial Area, Nepal. The study utilized a quantitative method with a descriptive design, which surveyed 147 workers in the industry who attended health clinics. The findings highlighted significant issues, such as refractive errors and dry eyes which were primarily linked to office work and exposure to polluted and chemically hazardous work environments. Moreover, the study findings also highlight the importance of strengthening OSH policies, implementing worker safety programs, and introducing targeted interventions to improve health outcomes and enhance workplace productivity.